Strengthening mechanism of surface-modified SiCp/Al composites processed by the powder-in-tube method. Issue 17 (1st December 2019) - Gao, H.T.; Liu, X.H.; Qi, J.L.; Chen, J.Q.; Ai, Z.R.
Abstract: The powder-in-tube method was used to investigate the strengthening mechanism of surface-modified SiCp /Al composites at room temperature. A typical amorphous Al2 O3 layer was formed for the untreated SiCp /Al composite (CUSiC ). Obvious interfacial cracks were generated in the pre-oxidized SiCp /Al composite (COSiC ), because of the insufficient activation energy for the reaction between SiO2 and Al. Comparatively, the interfacial strength of the Cu-coated SiCp /Al composite (CCu-SiC ) was significantly enhanced by the formation of the CuAl2 phase. The composite reinforced by the low content Cu-coated SiC (6 wt%) exhibiting an ultimate strength of 196 MPa (+ 50.7% compared to the Al matrix) was processed by the low-speed and short-time ball milling process followed by the pack rolling at room temperature. For CUSiC, load transfer and grain refinement were the main strengthening mechanism. While for CCu-SiC, the precipitation strengthening of tiny CuAl2 phase (0.6 vol.%) contributed to 77% to the total strength increase.